Les Juifs du Maghreb à Toulouse des années 1950 à nos jours. Une insertion réussie ? - Colette Zytnicki (Les Cahiers de Framespa)
This paper describes the Jewish society in Toulouse and explains the transformation caused by the arrival of Jews from North Africa in the 1960s. It looks into the social integration process and identity reconstructions, from both private and public standpoints.